DAMPAK KONVERSI LAHAN PERTANIAN TERHADAP PEREKONOMIAN MASYARAKAT NAGARI SUNGAI NANAM KABUPATEN SOLOK - Rezi Utami Putri; Adil Mubarak (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This study describes theindicate that there are four factors that influence the conversion of productive agricultural land in Nagari Sungai Nanam, namely population factors, economic factors, social factors and weak government policies towards agricultural land conversion. As well as several negative impacts felt by the Nagari Sungai Nanam community, including reduced job opportunities for farmers, reduced food production, reduced farmer income, decreased food availability, and higher food prices. As well as several positive impacts felt by the Sungai Nanam villagers, including an increase in the selling price of land around the area, construction of facilities and infrastructure such as roads and public facilities, and rapid development.